ANALISA N, P, K PADA PUPUK ORGANIK CAIR LIMBAH AIR TAHU DAN IKAN TERI SETELAH DEKOMPOSISI 30 HARI - Ulina Catarina Simatupang; Widya Lestari (JURNAL AGROPLASMA, 2021)
The aims of this study are to compare the feasibility of levels of Nitrogen, Phospor and Kallium liquid organic fertilizers resulting from anaerobic and aerobic, The results of 30 days of decomposition of organic waste made from raw water tofu and anchovy produce liquid organic fertilizer with levels of Nitrogen 0,30%, Phospor 0,18% and Kalium 0,10%. The Phospor content of liquid organic fertilizer produced from the decomposition of organic waste made from raw water tofu and anchovies has met the SNI 19-7030-2004 eligibility standards set by the ministry of agriculture so it is suitable for use on plants. Nitrogen and Kalium levels of liquid organic fertilizer obtained from the decomposition of organic waste made from water tofu, vegetables and fruit water with organic waste made from raw water tofu and anchovies not meet SNI 19-7030-2004 eligibility standards. Keywords: Nitrogen, Phospor, Kalium, Liqiud organic Fertilizers, SNI 19-7030-2004